(untitled) (Novateur Publications, 2023)
Currently, at textile and light industry enterprises, the detection of defective textile materials is one of the least automated stages of the technological chain. In most cases, heavy manual labor is used, where dozens of people are employed and a huge amount of working time is spent. These costs are not always effective. Improving the quality of products with minimal human labor costs is one of the main tasks in the development of the textile and light industry.